Potential ammonia volatilization from 39 different novel biobased fertilizers on the European market – A laboratory study using 5 European soils - Wester-Larsen, Lærke; Müller-Stöver, Dorette Sophie; Salo, Tapio; Jensen, Lars Stoumann (Elsevier BV, 2022)
Current political focus on promoting circular economy in the European Union drives great interest in developing and using more biobased fertilizers (BBFs, most often waste or residue-derived). Many studies have been published on environmental emissions, including ammonia (NH3) volatilization from manures, but there have only been a few such studies on BBFs. Ammonia volatilization from agriculture poses a risk to the environment and human health, causing pollution in natural ecosystems when deposited and formation of fine particulate matter (PMx). Furthermore, NH3 volatilization results in removal of plant-available N from agricultural systems, constituting an economic loss for farmers. The aim of this laboratory study was to determine the potential NH3 volatilization from 39 different BBFs commercially available on the European market. In addition, this study aimed to investigate the effect of incorporation, application rate, soil type, and soil moisture content on potential NH3 volatilization in order to derive suggestions for the optimal field application conditions. Results showed a great variation between BBFs in potential NH3 volatilization, both in terms of their temporal pattern of volatilization and amount of NH3 volatilized. The potential NH3 volatilization varied from 0% of applied total N (olive oil compost) to 64% of applied total N (manure and crop digestate) during a 27- or 44-day incubation period. Characteristics of BBFs (pH, NH4+-N, NO3−-N, DM, C:N) and their interaction with time could explain 89% of the variation in accumulated potential NH3 volatilization. Incorporation of BBFs into an acidic sandy soil effectively reduced potential NH3 volatilization by 37%–96% compared to surface application of BBFs. Potential NH3 volatilization was not significantly affected by differences in application rate or soil moisture content, but varied between five different soils (with different clay and organic matter content), with the highest NH3 volatilization potential from the acidic sandy soil.
Keywords: organic fertilisers; ammonia; nitrogen; (potential) Ammonia volatilization; Biobased fertilizers; Incorporation; Surface application; Incubation; Soil type